Sasaran Dakwah Pada Masa Nabi S.A.W: Kajian Khusus Tentang Keadaan Kemasyarakatan Orang Arab Jahiliah - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1996)
This article tries to expose the social system and daily customary rules among the Arab Jahiliyah, which is the first focus of the da'wah by the Prophet Muhammad s.a.w. It shows their inferior way of life which need to be changed immediately.